2015
DOI: 10.1007/s10071-015-0843-7
|View full text |Cite|
|
Sign up to set email alerts
|

Oxytocin enhances the appropriate use of human social cues by the domestic dog (Canis familiaris) in an object choice task

Abstract: It has been postulated that the neuropeptide, oxytocin, is involved in human-dog bonding. This may explain why dogs, compared to wolves, are such good performers on object choice tasks, which test their ability to attend to, and use, human social cues in order to find hidden food treats. The objective of this study was to investigate the effect of intranasal oxytocin administration, which is known to increase social cognition in humans, on domestic dogs' ability to perform such a task. We hypothesised that dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
84
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(98 citation statements)
references
References 39 publications
8
84
1
5
Order By: Relevance
“…Relatedly, the oxytocin-receptor gene is reported to be different between bonobos and chimpanzees [60]. Also see recent studies that showed the human-dog bonding and communication mediated by eye-contact, human social cues, and oxytocin [61, 62]. In humans, individuals with a higher level of prenatal androgens show a decreased level of eye contact [63].…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, the oxytocin-receptor gene is reported to be different between bonobos and chimpanzees [60]. Also see recent studies that showed the human-dog bonding and communication mediated by eye-contact, human social cues, and oxytocin [61, 62]. In humans, individuals with a higher level of prenatal androgens show a decreased level of eye contact [63].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been recently argued that this hormone modulates the multimodality that characterizes our higher-order linguistic abilities [Theofanopoulou, 2016]. Oxytocin promotes social play in domestic dogs and the appropriate use of human social cues [Oliva et al, 2015;Romero et al, 2015]. A positive correlation between SZ progression and oxytocin levels in the central nervous system has been observed [Beckmann et al, 1985], and it is plausibly explained by a decreased sensitivity to the hormone [Glovinsky et al, 1994;Sasayama et al, 2012;Strauss et al, 2015].…”
Section: Behavioral Traits and Neuroendocrine Impairmentmentioning
confidence: 99%
“…Recent research has found that polymorphisms in the oxytocin receptor (OXTR) 66 gene are related to human directed social behaviours in dogs (Kis et al, 2014a) and that 67 intranasally administered oxytocin promotes positive social behaviours toward both humans 68 and conspecifics (Romero et al, 2014). It has also been reported that intranasally 69 administered oxytocin induces positive expectations about ambivalent stimuli in dogs, 70 especially in a social context (Kis et al, 2015), enhances dogsʼ use of human pointing 71 gestures (Oliva et al, 2015), and increases gazing behaviour of female dogs to their owners in 72 a neutral situation (Nagasawa et al, 2015). However, no study has yet investigated the effect 73 of intranasal oxytocin on dogs' behaviour in negatively valenced situations.…”
Section: Introduction 41mentioning
confidence: 99%